Development of a Smash Training Model in Volleyball Games for Extracurricular Participants at SMA Negeri 3 Seluma - Raibowo, Septian; Pramadinata, Annisa; Yarmani; Permadi, Andes (CV Media Inti Teknologi, 2025)
This study aims to develop a smash training model for extracurricular volleyball game participants at SMA Negeri 3 Seluma. This research uses a Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The method used is descriptive qualitative. The study population consisted of volleyball extracurricular participants. The sampling technique used in this study was total sampling. Research instruments include observation, interviews, questionnaires, and documentation. Based on the validation results from material experts, linguists, and media experts, the following percentages were obtained: Material experts 92%, linguists 90%, and media experts 90%. The results of the small group trial involving 10 students showed an average percentage of 84%, while the large group trial with 20 students resulted in an average percentage of 91%. According to the results of this study, it can be concluded that the Smash Training Model for Volleyball Extracurricular Participants at SMA Negeri 3 Seluma is